Mit o “svetim trokutima” temeljenima na “sunčevom kutu” – analiza “astronomije” ranih Slavena - Bilić, Tomislav (Studia mythologica Slavica, 2020)
A number of interconnected scholarly publications discussing the phenomenon of the so-called sacred triangles have appeared lately. The authors who believe in the existence of this phenomenon argue that such triangles are based on a precisely determined value of the obliquity of the ecliptic. However, a detailed analysis of some of the key tenets discussed in their publications has revealed the gratuitous nature of this hypothesis, as well as its fundamentally unscientific character and the methodological flaws inherent in its overall development. Especially worrying is the falling into the pitfall of circular argumentation (circulus vitiosus) by the authors adhering to this hypothesis, their avoidance of any dialogue with relevant scholarly literature and their questionable understanding of fundamental phenomena upon which their hypothesis is built. A glaring example of the lattermost is the misunderstanding of the obliquity of the ecliptic on the part of the adherents of the so-called sacred triangles hypothesis.